Development of New Strategies Using Extracellular Vesicles Loaded with Exogenous Nucleic Acid - Nicola Salvatore Orefice (MDPI AG, 2020)
Gene therapy is a therapeutic strategy of delivering foreign genetic material (encoding for an important protein) into a patient's target cell to replace a defective gene. Nucleic acids are embedded within the adeno-associated virus (AAVs) vectors; however, preexisting immunity to AAVs remains a significant concern that impairs their clinical application. Extracellular vesicles (EVs) hold great potential for therapeutic applications as vectors of nucleic acids due to their endogenous intercellular communication functions through their cargo delivery, including lipids and proteins. So far, small RNAs (siRNA and micro (mi)RNA) have been mainly loaded into EVs to treat several diseases, but the potential use of EVs to load and deliver exogenous plasmid DNA has not been thoroughly described. This review provides a comprehensive overview of the principal methodologies currently employed to load foreign genetic material into EVs, highlighting the need to find the most effective strategies for their successful clinical translation.